Draft Annual Plan 1975-76 Vol. II Government of Manipur - Planning Commission (Planning Commission, 1974)
The Fifth Plan outlay of the Manipur State is tentatively of the order of Rs. 92„8 crores of which an outlay Rs. 25.22 Crores' has been proposed for the Annual Plan, 1975-76. The Draft Annual Plan. 1975-76, has been presented in three Volumes. Volume-I is in narrative- learn contains seven chapters. The introductory chapter gives overt. I survey of the socio-economic situation of the State with measuring proposer, to be- taken to make c-pitiful use of the Unviable resources. Chapter II gives the resources of the State, who the sector, Programmers have been discussed in Aortic in Chapter-III. I Programme the procaine of Hill/Tribal areas have been uncut the fourth and fifth chapters respectively. Also, a separate chapter has been added,, dealing with the problems of ad remedial measures against Natural Calamities. Lastly, the Administrative Policy and Institutional framework arc dealt in chapter VII.
Government of Manipur
Planning & Development Department
Keywords: Government of Manipur; Forest Research Education & Training; Plantation Scheme; Economic Plantation; Communication & Building; Preservation of Wild Life; Forest Management; Development of Minor; Public Relation Unit; Consolidation